(3SbW GdRfOs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s ((3eMeO Hf CHj HcQ Hf eMeO GdJaJGRGfi s)
(3ChdgG (B:s
(3CeG HYO aEf GdTYQGA cCaQGS JJSGHbjf ai eOi eG bUQ egG dMb heG hba dje hSHb s
(3BNQgG (B:s
(3Je SbW GdRfO Sei HPdc dCfg Chd eG jNQL ef fGQg hgPG bjd ai UOQ GdYeQ hGddg GdeSFhd ai GdJLGhR Yfg hYf ZjQg hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3fSNI fajSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
Keywords: (3GdCOHs